Género y activación de vocabulario. Entre la estereotipación y la normalización de los nuevos roles - Pierrot (Mulheres no Discurso - Women in Discourse, 2025)
This article presents the main results of a research project that has analysed the impact of the independent variable “gender” in relation to the sociocultural prompts “woman” and “man”. To do so, following the usual methodology of lexical availability in the Hispanic context, established by the Pan-Hispanic Lexical Availability Project, associative tests have been applied in Spanish to a group of undergraduate students in languages (N=30), of different nationalities, who were taking the subject of Spanish B2.2 at FLUP in the 2023-2024 academic year. For the purposes of contextualizing the data collection, they were previously given the reading of the poem “March 8” by Gioconda Belli as input. The results of our study confirm the influence of sociocultural elements in the activation of the informants' available vocabulary (already pointed out by researchers such as Pacheco Carpio, Cabrera Albert and González López, 2017) and show that, in parallel with a relative normalization of the new gender roles, certain stereotypes persist, which, by influencing the students' perceptions and attitudes, are also unconsciously reflected in their lexical selection.